ROADSIDE GREENBELT EFFECTS ON THERMAL COMFORT OF PEDESTRIAN CORRIDORS AT A BUSY TRAFFIC ROAD - Simangunsong, Nur Intan; Fauzi, Reza; Danniswari, Dibyanti; Fitri, Rini (Journal of Environmental Science and Sustainable Development, 2023)
The increasing number of motorized vehicles in Jakarta is causing environmental damage and can harm human health. In recent years, the Jakarta local government has the vision to focus on improving the human mobility network, including the pedestrian networks. As a heavily trafficked road, Jalan Kyai Tapa, West Jakarta, is used by many people. However, it may feel uncomfortable to walk there due to heat and sun exposure, which is compounded by extensive pavement coverage. The thermal condition of the pedestrian corridor is essential to create a comfortable walking experience. The objective of this study was to analyze the thermal comfort of the pedestrian corridors at Jalan Kyai Tapa concerning the landscape composition, including vegetation structure and pavement. This study was conducted quantitatively. This study identified the vegetation structure, including the tree species, canopy diameter, and height. Then, we measured the air temperature and relative humidity at predetermined measurement points to evaluate thermal comfort using the Temperature Humidity Index (THI). The results showed that the air temperature ranges from 31.01°C to 31.54°C, and the relative humidity ranges from 56.19% to 57.74%. The average THI value is 28.52 °C, which falls into the comfortable category. Despite having relatively wide canopies and providing shade, the trees in this pedestrian corridor do not seem to improve the thermal environment enough to achieve comfortable conditions for pedestrians. Interestingly, the result shows that, at certain observation times, points without trees had lower air temperatures compared to other spots with trees. Trees may not be the most influential factor in improving pedestrian thermal comfort. Furthermore, the spots near trees with more expansive canopies can be less comfortable than spots near trees with smaller canopies. Tree species and the planting spacing determine the efficiency of trees to improve thermal comfort.